Acute Toxicity Studies of Thai Herbal Preparation “Sao Thong Tai” in Animals: Sao Thong Tai - Lin, Chakariya; Pattaraarchachai, Junya; Kammal Pawa, Kumar; Wongyai, Surapote (Science & Technology Asia, 2020)
The objective of the present study was to investigate acute oral toxicity of the Thai herbal preparation “Sao Thong Tai” in vivo. The study included two experiments: one was twenty healthy albino mice administered with “Sao Thong Tai” extract, each at 2,000 mg/kg body weight; the other was thirty Wistar rats administered with “Sao Thong Tai” extract, each at 2,000 mg/kg and 5,000 mg/kg body weight. The overall observation period was 14 days. During the observation period all mice and rats survived and there was no sign of toxicity. All mice and rats appeared normal and gained weight and no mortality occurred. Necropsy findings at termination did not show any significant gross pathological lesions. In conclusion, the treated mice and rats did not show toxicity of “Sao Thong Tai”. The Thai herbal preparation “Sao Thong Tai” extract was recognized as safe and non – toxic, and therefore can be used for applications of traditional medicine in modern complementary and alternative therapeutics in humans.